Determining type 2 diabetes risk factors for the adults: A community based study from Turkey. Issue 5 (October 2018) - Cosansu, Gulhan; Celik, Selda; Özcan, Seyda; Olgun, Nermin; Yıldırım, Nurdan; Gulyuz Demir, Hulya
Highlights: T2D is a disease that hides itself and continued existence for many years without displaying any symptoms. Community-based risk determining studies are important in countries with increasing diabetes rate. FINDRISC can be used as screening tool to identify individuals at high risk for diabetes. Abstract: Aims: This study aimed to determine risk factors for type 2 diabetes among adults who were not diagnosed with diabetes. Methods: Adults were included in this study within the public activities performed on World Diabetes Day (n = 1872). Data were collected using the FINDRISC questionnaire and a short questionnaire. Results: Participants' mean age was 39.35 ± 10.40. The mean FINDRISC score was 7.46 ± 4.62, women's mean score was higher than that for men. The FINDRISC score indicates that 7.4% of the participants were in the highrisk group. Among participants, BMI value of 65.1% was 25 kg/m 2 and higher, waist circumference of 58% was over the threshold value; and 50.7% did not engage in sufficient physical activity. Of the participants, 9.5% had a history of high blood glucose, families of 38.9% had a history of diabetes. The mean FINDRISC score was in the slightly high category, 121 participants were found likely to be diagnosed with diabetes within ten years if no action was taken. Conclusions: It is recommended the risk screening studies to be conducted and the FINDRISC tool to be used in Turkey, where diabetes prevalence is increasing rapidly, to determine diabetes risks in the early period and to raise social awareness for diabetes.